The role of cash waqf in property alleviation: case of Malaysia - Saifuddin, Farhah; Kayadibi, Saim; Polat, Refik; Fidan, Yahya; Kayadibi, Omer (2014)
Poverty alleviation has always been one of the biggest challenges faced by the Malaysian government. Since the establishment of the New Economic Policy in the 1970s, the battle faced by the Malaysian government against poverty continues up till today. Although the current government policies used for eradicating poverty have lead to favourable results, the government, private sector and NGOs are always in the lookout for other new strategies that could be used as one of the tools to alleviate poverty. The emergence of cash waqf in Malaysia, gives a different light to the formulation of strategies that can be used in improving the quality of lives of the ones burdened by poverty. The rapid development of cash waqf in Malaysia has reached great lengths in these recent years. The increasing awareness among the general public is one of the contributing factors to this phenomenon. The religious state department and waqf centers in Malaysia are also active in developing more contemporary waqf instruments that are beneficial to the general public. This increases the prospects of cash waqf to play a more prominent role in poverty alleviating initiatives in Malaysia. In the light if this issue, the objective of this paper is to look into the potential of integrating cash waqf with the poverty alleviation initiatives in Malaysia. Besides that, this paper also attempts to analyze other forms of cash waqf utilization, beyond religious purposes.